Pengaruh Pupuk Kandang Ayam dan Pupuk P terhadap Pertumbuhan dan Hasil Kubis Bunga (Brassica oleracea L. var. botrytis) - Tarigan, Shonry Roy KH Malem; Rusmarini, Umi Kusumastuti; Setyorini, Titin (Program Studi Agroteknologi INSTIPER, 2024)
The aims of this research was to determine the impact of chicken manure and P fertilizer on the development and production of cauliflower. This research was done from February to April 2023 in Pakis, Magelang This study used a completely randomized design (CRD) which includes 2 factors. Factor A uses chicken manure with a measurement of 3 types, such as 200 g, 400 g, 600 g. Factor B uses P fertilizer with a dose of 3 types, such as 20 g, 30 g, 40 g. Each treatment combination was repeated 3 times. The research data using a real level analysis of 5%. If there is a significant difference in the treatment, it will be held using the Duncan Multiple Range Test. The results of the study explained that there was an interaction in the dose of chicken manure with P fertilizer on the parameters of flower circle. The best treatment combination for flower circle parameters was 400g of chicken manure and 40g of P fertilizer. The application of chicken manure with doses of 200g, 400g, and 600g produced a similar effect on the development and production of cauliflower. The application of P fertilizer at a doses of 20g, 30g, 40g have produced the same a similar effect on the growth and yield of cauliflower.